Climate compatible development in practice. Issue 2 (17th February 2022) - Robinson, Stacy-ann; Carlson, D'Arcy; Messer, Anna; Maunus, Lauren; Bouton, Emma; Roberts, J. Timmons
ABSTRACT: Climate compatible development (CCD) is a deliberate policy framework that reduces climate-related harm while increasing development opportunities when its three components – adaptation, mitigation, and development – are pursued jointly. In this viewpoint article, we use three island case studies – urban infrastructure improvements in the Solomon Islands, clean energy transitions in Hawaii, and sustainable tourism in the Seychelles – to argue that, in practice, CCD is not always deliberate and that a focus on one component can have unintended but positive outcomes for the others. These case studies illustrate the potential for "triple wins", including lower emissions, increased resilience, and accelerated development.